The effect of bacterial and archaeal populations on anaerobic process fed with mozzarella cheese whey and buttermilk. (1st July 2018) - Pagliano, Giorgia; Ventorino, Valeria; Panico, Antonio; Romano, Ida; Robertiello, Alessandro; Pirozzi, Francesco; Pepe, Olimpia
Abstract: Dairy wastes can be conveniently processed and valorized in a biorefinery value chain since they are abundant, zero-cost and all year round available. For a comprehensive knowledge of the microbial species involved in producing biofuels and valuable intermediates from dairy wastes, the changes in bacterial and archaeal population were evaluated when H2, CH4 and chemical intermediates were produced. Batch anaerobic tests were conducted with a mixture of mozzarella cheese whey and buttermilk as organic substrate, inoculated with 1% and 3% w/v industrial animal manure pellets. The archaeal methanogens concentration increased in the test inoculated at 3% ( w/v ) when H2 and CH4 production occurred, being 1 log higher than that achieved in the test inoculated at 1% ( w/v ). Many archaeal species, mostly involved in the production of CH4, were identified by sequencing denaturing gradient gel electrophoresis (DGGE) bands. Methanoculleus, Methanocorpusculum and Methanobrevibacter genera were dominant archaea involved in the anaerobic process for bioenergy production from mozzarella cheese whey and buttermilk mixture. Graphical abstract: Image 1 Highlights: The key archaeal species involved in H2 and CH4 production were identified. Dairy wastes are suitable byproducts for being valorized in a biorefinery process. Inoculum significantly influenced microbial dynamics and process performance. Microbial dynamic and biochemical intermediate were considered and related. Higher inoculum amount increased methanogens concentration of 1 log CFU/mL.